Statistical models to identify significant crop-logging parameters influencing crop-yield across various growth stages in brinjal (Solanum melongena) - HANUMANTHAIAH, R; VENUGOPALAN, R; GOWDA, D M; PADMINI, K; MANJUNATH, V; MALLIKARJUNA, G B; THIPPESWAMY, S (The Indian Journal of Agricultural Sciences, 2014)
Crop-logging models developed showed that brinjal (Solamun melogena L.) crop yield could be predicted well in advance as early as 26 DAP using three biometrical traits (plant height, plant girth and plant spread north south ) to an extent of 71 %. As the DAP increases prediction of yield could be possible to an extent of 88%. Identification and removal of outliers in data set increased the prediction of models in the range of 31%, 33%, 34 and 8% respectively across four crop growth stages.